2020
DOI: 10.1002/adhm.202000236
|View full text |Cite
|
Sign up to set email alerts
|

Additive Manufacturing of a Point‐of‐Care “Polypill:” Fabrication of Concept Capsules of Complex Geometry with Bespoke Release against Cardiovascular Disease

Abstract: Polypharmacy is often needed for the management of cardiovascular diseases and is associated with poor adherence to treatment. Hence, highly flexible and adaptable systems are in high demand to accommodate complex therapeutic regimens. A novel design approach was employed to fabricate highly modular 3D printed 'polypill' capsules with bespoke release patterns for multiple drugs. Complex structures were devised using combined fused deposition modelling 3D printing aligned with hotfilling syringes. Two unibody h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 46 publications
0
42
0
Order By: Relevance
“…In combination with medical imaging techniques, three dimensional (3D) printing technologies [6][7][8][9][10][11][12][13] , such as digital light processing (DLP) 14 , provide enormous opportunities for rapid and affordable production of personalized medical devices [15][16][17][18][19] , including airway stents 5 . This specific manufacturing technology is based on the localized light-initiated photopolymerization of a liquid resin containing (macro)monomers 6,20 .…”
Section: Introductionmentioning
confidence: 99%
“…In combination with medical imaging techniques, three dimensional (3D) printing technologies [6][7][8][9][10][11][12][13] , such as digital light processing (DLP) 14 , provide enormous opportunities for rapid and affordable production of personalized medical devices [15][16][17][18][19] , including airway stents 5 . This specific manufacturing technology is based on the localized light-initiated photopolymerization of a liquid resin containing (macro)monomers 6,20 .…”
Section: Introductionmentioning
confidence: 99%
“…The capsule shell composed of polyvinyl alcohol and polylactic acid. Customized release profiles were obtained through the alteration of shell thickness in the concentric configuration or size of rate limiting orifices in the parallel configuration ( 134 ).…”
Section: Potential Of 3d Printing In Personalized Medicinementioning
confidence: 99%
“…However, patients require different doses and combinations of medicines and a rigid formulation would only be suitable for a very limited number of patients. 11 One proposed solution is to use 3D printing as a way to quickly and easily manufacture personalized polypills at pharmacy level. 3D printing has the capability to create highly modular capsules which allow for bespoke drug release patterns by controlling concentric shell thickness or shell porosity.…”
Section: Burden Relief For Polypharmacy Patientsmentioning
confidence: 99%
“…10 These issues may be exacerbated for patients requiring polypharmacy (40-50% of elderly patients in high-income countries) where >25% of elderly patients have a chronic intake of 10+ medicines. 11,12 Polypharmacy can impact adherence through myriad drivers including increased financial burden, unwanted drugdrug interactions, and complex/difficult dosing regimens. Studies have shown that a patient's perceptions on the number of prescribed medications have a stronger correlation with low adherence than the actual number, making polypharmacy a complex issue to tackle.…”
Section: Introductionmentioning
confidence: 99%